Motor skill acquisition: Specificity or general rule learning? - Vass, Z. (International Journal of Computer Science in Sport, 2002)
According to the results of the recent experimental research, which deals with the nature of motor control. The researchers strongly believe that, motor learning means general rule learning and not specification. Due to this fact, the special movement control units are missing out of these theories. Studying the quick, discrete movement execution the opposing statement has come out, according to that in this kind of movement the motor learning means specialization, which can be detected by the precision and automatization of the movement. In this paper we suggest to implement a special motor program into the motor control theories, which could give overall explanation for the control of quick, discrete movement. The aim of this article is to prove the existence of the special motor program, which suggested by us in the framework of a motor learning process. A well observed and defined movement served to prove the existence of this special unit. The subjects were asked to make a quick extention-flexion in their elbow joint using their palm to generate a vacuum to blow out a candle without any direct connection with the flame. The experimental order, the quick execution of the movement and the high number of the execution assured to analyze the connection between the generalized motor program, the special motor program (suggested by us) and the forward model. 6 sport university students were participated in this experiment. Their age is between 22-27 and all of them are active as sportsmen. One hand the aim of this experiment is to demonstrate during the motor acquisition process at the mentioned quick, discrete movement means specialization instead of general rule learning.